Opportunities for improvement of distal autologous reconstructions in patients with chronic critical limb ischemia - O. I. Gudz (Zaporožskij Medicinskij Žurnal)
Study objective: to evaluate the diagnostic capabilities of spiral CT-angiography (CTA) for planning of autovenous distal arterial reconstruction (DAR) and to develop intraoperative techniques aimed at reducing the negative effect of traumatic processes of harvesting and preparation of the great saphenous vein in patients with chronic critical limb ischemia (CCLI).